The STAT3/TIMP1 inhibitor silibinin overcomes secondary immunoresistance to pembrolizumab in brain metastases from METex14 skipping mutated non-small cell lung cancer: a case report - Joaquim Bosch-Barrera; Joaquim Bosch-Barrera; Joaquim Bosch-Barrera; Elia Sais; Elia Sais; Elia Sais; Eduard Teixidor-Vilà; Eduard Teixidor-Vilà; Carmen Vásquez-Dongo; Carmen Vásquez-Dongo; Alejandro Hernandez-Martínez; Alejandro Hernandez-Martínez; et al. (Frontiers in Medicine, 2025)
BackgroundApproximately 20% of patients with non-small cell lung cancer (NSCLC) are diagnosed with brain metastases (BM), which are associated with poor prognosis. Pembrolizumab has shown promising results in advanced NSCLC with PD-L1 ≥ 50%, including patients with BM. Silibinin is a flavonolignan with known blood-brain barrier permeability and anti-BM activity associated with inhibition of the STAT3/TIMP1 signaling axis. To the best of our knowledge, this is the first clinical evidence of combining silibinin with pembrolizumab to achieve a durable partial response in BM, lasting over 9 months.Case ReportWe present the case of a 72-year-old male with stage IVB lung adenocarcinoma and BM, who achieved durable intracranial tumor control with a combination of pembrolizumab and silibinin supplementation. Initial treatment with brain hypofractionated stereotactic radiotherapy and pembrolizumab led to a 14-month partial response. Progression occurred with a new jejunal metastasis and increasing temporal brain lesion. After declining whole-brain radiotherapy, the patient continued pembrolizumab with silibinin (630 mg/day), on a compassionate basis. At 2 months, a partial response in the temporal lobe lesion was observed, and at 9 months, nearly complete intracranial response was achieved with no extracranial progression. Molecular analysis revealed high PD-L1 expression and a METex14, potentially enhancing the response to immunotherapy.ConclusionThis case highlights the potential of silibinin as an adjuvant therapy to enhance anti-PD-1 efficacy in brain metastases, possibly by targeting STAT3/TIMP1-driven immunosuppressive astrocytes. Further investigation of the role of silibinin in improving immunotherapy outcomes in advanced lung cancer patients with BM is required.